Effect of comprehensive psychosomatic promotion in hypertension patients with anxiety and depression based on community: A randomized parallel controlled trial. Issue 33 (14th August 2020) - Zhang, Hailiang; Jiang, Xiaomei; Da, Haixia; Dai, Runjing; Zhao, Na; Pan, Weimin; Fan, Jingchun
Abstract: Background: Mental health is closely related to the occurrence of hypertension, particularly the prognosis of hypertension patients. The role of psychotherapy in the occurrence, development, prevention, and prognosis of hypertension, remains to be clarified. Methods/design: We will conduct a prospective, double-blind, randomized, multiple-centers study. Eighty patients enrolled in this trial will be randomized at 1:1 ratio. The primary endpoint is will be the reduction of the patient psychological scale (PHQ-9) score. Secondary endpoints will be the drop in blood pressure, awareness of physical and mental health and self-efficacy scale. Measurements will be performed at baseline, 5-week (questionnaires only), 10-week (primary endpoint), using the Anxiety Screening Questionnaire (GAD-7) and Depression Scale (PHQ-9). Data analysis will be carried out using the SPSS v.25 software assuming a level of significance of 5%. Results will be analyzed using multilevel, regression analysis and hierarchical linear models. Discussion: We hope to provide some insight in the understanding the underlying mechanism of the novel mindfulness in the management of hypertension related psychological stress/disturbance, and will enable us to develop novel approach to manage essential hypertension and its related psychological disorders. Clinical trial registry: http://www.chictr.org.cn (ChiCTR1900028258)